2019
DOI: 10.1371/journal.pone.0216465
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 downregulates zymosan-induced neutrophil activation and modulates migration

Abstract: Polymorphonuclear neutrophils (PMNs) are the first line of defense against pathogens and their activation needs to be tightly regulated in order to limit deleterious effects. Nrf2 (Nuclear factor (erythroïd-derived 2)-like 2) transcription factor regulates oxidative stress and/or represses inflammation in various cells such as dendritic cells or macrophages. However, its involvement in PMN biology is still unclear. Using Nrf2 KO mice, we thus aimed to investigate the protective role of Nrf2 in various PMN func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 65 publications
(93 reference statements)
1
11
0
Order By: Relevance
“…For leukocytes, it has been shown that SFN is able to alter leukocyte adhesion. Moreover, it is suggested to play a role in the regulation of pro-inflammatory cytokines and, through the role as Nrf2-agonist, required for optimal migration of neutrophils [40]. In accordance with the here presented data, a study of LPS-induced inflammation in the brain could show a decrease in leukocyte adherence as well as reduced MPO levels after pre-treatment with SFN [41].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For leukocytes, it has been shown that SFN is able to alter leukocyte adhesion. Moreover, it is suggested to play a role in the regulation of pro-inflammatory cytokines and, through the role as Nrf2-agonist, required for optimal migration of neutrophils [40]. In accordance with the here presented data, a study of LPS-induced inflammation in the brain could show a decrease in leukocyte adherence as well as reduced MPO levels after pre-treatment with SFN [41].…”
Section: Discussionsupporting
confidence: 90%
“…While leukocyte recruitment is an important aspect in inflammatory response, excessive accumulation during I/R contributes to pathological conditions [38,39]. Recent studies have shown the ability of SFN to affect cells of the innate immune system including neutrophils and platelets that are known as the first line defense following injury [20,40]. For leukocytes, it has been shown that SFN is able to alter leukocyte adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were collected from the femur and tibia and resuspended in PBS solution containing 0.5% bovine serum albumin (BSA) and 2 mM Ethylene diamine tetraacetic acid (EDTA) [ 28 , 29 ]. Collected cells were filtrated through 70 μM pre-separation filters to remove cell aggregates or large particles.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, NRF2 activators inhibit also the transcriptional activity of NF-κB and the inflammasome pathway (see below) [19,22]. The expression and activity of NRF2 is very high in immune cells, which are frequently exposed to oxidative stress, particularly upon induction of the oxidative burst during phagocytosis of pathogens [47]. However, epithelial keratinocytes also express high levels of NRF2 and the transcription factor is critically involved in wound healing [4], UV protection [3,5], skin cancer development [48] and several severe autoimmune diseases with skin involvement, such as systemic lupus erythematosus, Sjogren's syndrome and vitiligo [19].…”
Section: Nrf2 Is Activated By Electrophiles Upon Cysteine Oxidation Omentioning
confidence: 99%